Analisis kualitas fisika kimia air di areal budidaya ikan Danau Tondano Provinsi Sulawesi Utara - Maniagasi, Richard; Tumembouw, Sipriana S.; Mudeng, Yoppy (Universitas Sam Ratulangi, 2013)
ABSTRACT The objective of this research was to analyse the water physical-chemical qualities at aquaculture area in Lake Tondano North Sulawesi. Water quality was measured in situ and in laboratotium. In situ measurement included temperature, pH, and turbidity, while in laboratory, water quality measured included dissolved oxygen, nitrogen, phosphate. It was found that water temperature ranged from 25 - 27 o C, turbidity 0.20 - 4,0 m, and dissolved oxygen 5 – 9 mg/L, Nitrogen 0,0334 - 0,0697 mg/ L, phosphate 0 - 0,0219 mg/ L. It was concluded that water quality around Paleloan Village was appropriate for aquaculture activity. Keywords: water quality, aquaculture, Paleloan Village